Taxonomic assessment of Diporiphora (Reptilia: Agamidae) dragon lizards from the western arid zone of Australia - Doughty, Paul; Kealley, Luke; Melville, Jane (Zootaxa, 2012)
Members of the genus Diporiphora are slender perching agamid lizards from Australasia, with a conservative morphologyand some outstanding taxonomic issues. Here we assess morphological variation in the morphologically similar D. pin-dan, D. valens, and D. winneckei from the western deserts of Australia. A reassessment of morphological differences thatincluded the presence or absence of a gular fold, revealed D. pindan to be much more widely distributed than previouslythought, occurring as far south as the northern Pilbara and east to the Tanami Desert. Examination of D. valens specimensrevealed a north-south split within the Pilbara, with specimens conspecific with the types from the Hamersley Range inthe southern Pilbara, whereas recently collected specimens from the Chichester and Roebourne regions in the northernPilbara differ morphologically, and are described as a new species. Examination of the type of D. winneckei and topotypicmaterial indicates that populations referable to this species are confined to the eastern arid zone. The isolated far westernpopulation of ‘D. winneckei’ from the Carnarvon Basin differs in morphology from the eastern arid zone D. winneckei andis described as a new species. The western arid zone ‘D. winneckei’ is also morphologically distinctive from the easternarid zone D. winneckei and is described as a new species. We also redescribe D. pindan, D. valens, and D. winneckei, and return Caimanops amphiboluroides to Diporiphora based on the results of previous genetic studies.